PENGARUH HARGA SAHAM, VOLUME PERDAGANGAN, DAN FREKUENSI PERDAGANGAN TERHADAP BID-ASK SPREAD - Rahma Nurul Khoirayanti; Hari Sulistiyo (Universitas Pakuan, 2020)
This study aims to determine the effect of stock prices, trading volume and trading frequency on the bid-ask spread of companies listed in the LQ-45 Index. This type of research is descriptive verification research. The population of this study is all companies listed on the Indonesian stock exchange (BEI). The research sample was selected using purposive sampling method in order to obtain 10 sample companies. Data analysis using multiple regression analysis. The results showed that the stock price had no effect on the bid-ask spread, while the volume and frequency of trading had an effect on the bid-ask spread. In addition, if the independent variable simultaneously affects the dependent variable. The implication of this research is that companies really need to pay attention to the level of trading volume and trading frequency because these ratios are very influential on investors' perceptions.